A design on centrifugal ice breaking and snow removal system based on ADAMS. Issue 2 (23rd February 2017) - Wang, Gang
ABSTRACT: In this thesis, a new centrifugal ice breaking and snow removal system is designed to solve the problems of ice and snow removal machines, such as low efficiency, poor pavement protection ability and high cost. This system is composed of centrifugal ice breaking unit, drive unit, adaptive unit, walking unit and ice shovel and snow removal unit. This system uses the rotation trundle to drive the rotation of the ice breaking hammer jointed by the hinge and the ice layer will be scrapped after the kinetic energy of the ice breaking hammer reaches the critical damage the ice breaking needs so as to attain the goal of ice breaking; it uses the rotate mode to load the round brush or rolling shovel to remove ice and snow. Different functions can be realized through shifting function keys. During the design process, the ADAMS software is used to make the 3D simulation model and the data acquired through simulation are used to optimize the structure design in order to improve the efficiency and quality of system design. GRAPHICAL ABSTRACT: